The Development of Student Care and Support System Performance of Anukoolnaree School under Kalasin Secondary Educational Service Area Office - Chaicammee, Weerapol; Cain, Parisha Marie; Duangnet, Supot (Journal of Education Rajabhat Maha Sarakham University, 2024)
The purposes of this action research were to 1) study the performance of the student support system of Anukoolnaree school, kalasin secondary education area office, and 2) develop the operation system process. The research informant group consists of the school administrators, teachers, and the classroom leaders. The research tools were questionnaires, consultation meeting minutes, an interview forms, a student support system operation manual assessment form, and an activities performance analysis form. The data analysis used mean and percentages. The qualitative data usesd content analysis and presented the data descriptively. The results of the research showed that: 1) The overall for the current operating conditions of the student care and support system were at high level. When it was considered individually, it was also at high level in all aspects: knowing students individually, screening students, transferring students, encouraging and developing students. Prevention and problems solving. The overall for development needs was at high level. When it was considered individually, it was also at high level in all aspects; namely knowing the students individually, student screening, student promotion and development, problems solving, and student referral., and 2) The assessment results of the system development operation process were at the highest level, because of these reasons: The researcher analyzed, synthesized the data from the study of current operating conditions and the sample’s needs, then developed the system,operation processes, then completed the manual, until the manual was assessed by the the experts before using the system at the school.